Vistas in Physical Reality
XII, 228 p. 3 illus.
Keywords: Festschriften, when they are haphazard collections of pieces written by colleagues and well-wishers on the occasion of a major anniversary in the life of a distinguished man, tend to be tedious. One can more profitably go directly to the writings of the celebrant, as well as other, more voluntary publications of his well-wishers. However, the editors wish to claim that this Festschrift is different. This is so first of all because of the almost unique combination of interests and competence of Henry Margenau. He is at once a distinguished physicist, an equally distinguished educator, and a prominent philosopher. These broad areas of his extraordinarily active and fruitful career are each represented in this volume in his honor, and this constitutes the particular interest of the collection. Without limiting themselves to paraphrases or empty compliments, the contributors to this book range over the scope of interest of Margenau's work, and, acknowledging its influence and significance, present their own viewpoints and conclusions. Since they include some of the most distinguished men in science and philosophy today, the privilege of having them speak to some broadly defined common concerns in a single volume is a rare one, for which our thanks must go to Henry Margenau, who inspired the papers.